Individual transferable quotas and the reform of European fisheries policy - Rui Junqueira Lopes; Filipe, J. A.; Ferreira, M. A. M.; Coelho, M. (Ensaios de Homenagem de João Ferreira do Amaral, 2013)
With the publication of the "Green Paper" on the Reform of the Commons Fisheries Policy, the European Commision is Launching a wjde consultation to the national administrators, stakeholdres, reswearchesrs and other interested people. The objectives are to discussthr problems of the actual CFP and to explore the alternatives and the ways forward the new reform of fisheries policy. The main purpose of this paper is to enter this debate, making the repertory of the maintained guidelines and the fundamental changes introduced in this reform; discussing and evaluating their relevance and potentialities, as well as their difficulties and risk factors. Besides, a special attention is given to the possibility of introducing a more focused approach on Rights Based Management, in the form of ITQs (Individual Transferable Quotas) in the managemnt regime.